Assessing students competencies and learning in master thesis projects: towards an integrated evaluation approach - Arisó, Albert; Girotto, Michele; Seguí Amórtegui, Luís (Journal of Management and Business Education, 2019)
This study is conducted in the context of a Spanish Business School, applied to different Master degree programme. The objective is focused on the identification of which generic skills are needed and developed in a Final master thesis (FMT). Therefore, this study is double folded. On the one hand we use a survey to ask the students which generic skills they consider that should be needed and developed in their FMT, and on the other, we explore the elaboration process as well as validation process of tools to gather information and evidences in order to assess the final results of the FMT being submitted by the students at the end of their learning journey. Specifically, this paper develops the preliminary results approach to the identification of the competencies from the student’s perspective.